Diseño e implementación de un taladro fresador para elevar el nivel de enseñanza práctica en el laboratorio de máquinas herramientas de la carrera de ingeniería en electromecánica de la Universidad Técnica de Cotopaxi extensión La Maná, año 2015 - Zambrano Enríquez, Carlos Paúl (2015)
This project is developed in order to implement a milling to raise the level of teaching students practice drill, allowing them to achieve the drilling and milling of countless parts that are common in industries. The milling process is based on theoretical and practical knowledge in the cathedras of mechanical workshop I and II. At present the institution does not have a suitable drill for workshop practice and demonstrate the theoretical knowledge acquired in the classroom. Faced with this problem this problem this research topic arose because it was made with the firm intention of clearing all theoretical concerns.